Brazil, Russia, India, China and South Africa: Strong economic growth - major challenges - Mechthild Schrooten (DIW Economic Bulletin, 2011)
Brazil, Russia, India, China and South Africa - the so-called BRICS countries - all show high economic growth rates. They suffered only shortly under the turbulences of the international financial crisis in 2008/2009 and were able to recover quickly - in contrast to most industrialized nations. In recent times of economic fragility in industrialized countries, the BRICS are playing a decisive role for global economic stabilization. The BRICS countries opt for different catching-up strategies. Although they have experienced remarkable growth rates over the past years, similar income levels like in the most important industrialized countries are still beyond reach in the medium term. Additionally, BRICS states still show considerable deficits in terms of access to education and regarding their health systems. Such infrastructural problems, however, can be important obstacles for future development.
Keywords: F02; O15; O57; 330; development; international economic order; human development; comparative studies of countries